Digital Services Tax: Challenge of International Cooperation For Harmonization - Machfud Sidik (LPPM-STPI, 2022)
The spread of the digital economy brings about many benefits, for example in terms of growth, employment and well-being more generally. These challenges extend well beyond domestic and international tax policy and touch upon areas such as international privacy law and data protection, as well as accounting and regulation, a strategic tax policy perspective, the uptake of digital technologies may potentially constrain the options available to policymakers in relation to the overall tax mix. Technological innovation and the growth of the Internet have profoundly affected trade relations, production processes and products, and the organization of companies. The digital economy is characterized by several key elements, such as the massive expansion of intangible assets; intensive use of data (especially personal data), and widespread adoption of multi-faceted business models that exploit the value externalities of free assets. As the digital economy brings us into new territory, is fair taxation fiction or reality? Although overcoming the numerous ch a l l en g es will be a difficult task for policy makers , fair taxation of the digital e c o n o m y is a reality. A prerequisite to making real sustainable change is enthusiastic country commitment and international cooperation. Asia and the Pacific region need to pull together and push forward the necessary reforms, innovate tax structures and administration, and continue to learn from each other’s experiences. Other key enablers include a coherent strategy and strong evidence-based communication and knowledge.